Politics in the European Union - Bache, Ian
"This text provides an accessible and comprehensive introduction to all aspects of the European Union, and the process of European integration. It covers at the core elements of an introductory undergraduate course on the European Union: theory, history institutions and policies." "The second edition has been thoroughly updated and revised, and combines a review of current academic debates with empirical date."--BOOK JACKET.